Female Independence in Mary Robinson’s The Natural Daughter - Watts, Katherine (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2012)
More provocatively than her contemporaries, Mary Robinson argues in The Natural Daughter that women must establish their voices in the public sphere to enact change while separately attending to the influential roles of wife and mother. She argues for financial independence and personal satisfaction by entering the public sphere through intellectual productions, such as writing. By examining Robinson’s concern for converging public and private spheres, we see a unique argument for women’s intellectual worth to be free of their reputations.